Horrid Henry and the abominable snowman - "Simon, Francesca" (Orion: London, 2007)
Building a snowman brings out Henry's competitive streak; he sets up his Monstrous Makeovers business to rival Moody Margaret's Miraculous Makeovers; things go badly wrong when a famous author comes to school; and he thinks 'You'll all be sorry when I'm dead' and spends a rainy day writing his will
Keywords: Snowmen Juvenile fiction